2001
DOI: 10.2134/jeq2001.303683x
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Site Movement of Endosulfan from Irrigated Cotton in New South Wales

Abstract: The fate and transport of endosulfan (6,7,8,9,10,10-hexachloro-1,5, 5a,6,9,9a-hexahydro-6,9-methano-2,4,3-benzodioxathiepin 3-oxide) applied to cotton (Gossypium hirsutum L.) fields were studied throughout three consecutive years on two selected locations in New South Wales (Australia). Rates of dissipation from foliage and soil, volatilization from the field, and transport of residues in irrigation and/or storm runoff waters were measured in order to estimate a total field balance. Dissipation of endosulfan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 26 publications
(35 reference statements)
7
67
0
12
Order By: Relevance
“…Our study did not differentiate whether residues were situated on outer surfaces of plant tissues or were taken up into the tissues of the plant. However, several authors have reported endosulfan residues, including metabolites, in, on, or in and on tomato plant tissues (Aguilera-del Real et al, 1997;, as well as in, on, or in and on tissues of other plants and in soil (Bead and Ware, 1969;Stewart and Cairns, 1974;Chopra and Mahfouz, 1977;Martens, 1977;Singh et al, 1991;Raha et al, 1993;Kennedy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study did not differentiate whether residues were situated on outer surfaces of plant tissues or were taken up into the tissues of the plant. However, several authors have reported endosulfan residues, including metabolites, in, on, or in and on tomato plant tissues (Aguilera-del Real et al, 1997;, as well as in, on, or in and on tissues of other plants and in soil (Bead and Ware, 1969;Stewart and Cairns, 1974;Chopra and Mahfouz, 1977;Martens, 1977;Singh et al, 1991;Raha et al, 1993;Kennedy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In both foliage and fruit, this breakdown product of endosulfan persisted until the termination of the experiment at 14 days. Oxidation of the parent compounds (Kennedy et al, 2001) causes an initial buildup in the sulfate metabolite, which reaches a peak in 6 and 2 days in foliage and fruit, respectively, after application. Given that endosulfan sulfate is formed in many natural environments through biological oxidation and that it is only slowly degraded, both chemically and biologically (Miles and Moy, 1978), it may represent a predominant residue of endosulfan in aerobic environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A presença de resíduos de agrotóxicos em amostras de água da chuva tem sido utilizada para demonstrar a volatilização desses compostos em países de clima temperado (Dubus et al, 2000;Vogel et al, 2008;Gish et al, 2011) e tropical (Laabs et al, 2002;Nogueira et al, 2012), inclusive com relatos da presença do endossulfam (Scheyer et al, 2005;Nogueira et al, 2012). Kennedy et al (2001) observaram volatilização de 70% do endossulfam após sua aplicação na cultura do algodoeiro, na Austrália.…”
Section: Methodsunclassified
“…O principal metabólito do endossulfam no solo após sofrer oxidação microbiológica, é o sulfato de endossulfam (Kennedy et al, 2001), que é altamente tóxico aos organismos aquáticos (Leonard et al, 2001) além de apresentar maior toxicidade aos seres humanos que o próprio endossulfam. Diante disto, o governo brasileiro determinou a proibição de seu uso a partir de 31 de julho de 2013 (ANVISA, 2010).…”
Section: Introductionunclassified